Mauriac's Syndrome is still among us: A case report (Research, Society and Development, 2025)
Mauriac's Syndrome (MS) is a rare complication of Type 1 Diabetes Mellitus (T1DM) triggered by inadequate glycemic control. The objective of this article is to present a classic case of MS, manifested in an insulin-dependent pre-pubescent diabetic, with typical symptoms and findings. Although its incidence has decreased with advances in T1DM management, MS remains clinically relevant. This study presents a case report of a 14-year-old male patient diagnosed with this condition after being referred to a specialized center, describing the findings observed during clinical evaluation and physical examination, laboratory and imaging tests, and the results of the liver biopsy performed, which confirmed the diagnosis. The presented case illustrates the persistence of MS in patients with poorly controlled T1DM, highlighting the need for healthcare professionals to be attentive to this rare but clinically significant complication. Early diagnosis and optimization of glycemic control are fundamental for the reversal of hepatic and systemic changes, as is the relevance of guiding the patient and their guardians for therapeutic success in this age group.